Directional cloning of DNA fragments using deoxyinosine-containing oligonucleotides and endonuclease V - Baumann, Tobias (BioMed Central, 2013)
BACKGROUND: DNA fragments carrying internal recognition sites for the restriction endonucleases intended for cloning into a target plasmid pose a challenge for conventional cloning. RESULTS: A method for directional insertion of DNA fragments into plasmid vectors has been developed. The target sequence is amplified from a template DNA sample by PCR using two oligonucleotides each containing a single deoxyinosine base at the third position from the 5′ end. Treatment of such PCR products with endonuclease V generates 3′ protruding ends suitable for ligation with vector fragments created by conventional restriction endonuclease reactions. CONCLUSIONS: The developed approach generates terminal cohesive ends without the use of Type II restriction endonucleases, and is thus independent from the DNA sequence. Due to PCR amplification, minimal amounts of template DNA are required. Using the robust Taq enzyme or a proofreading Pfu DNA polymerase mutant, the method is applicable to a broad range of insert sequences. Appropriate primer design enables direct incorporation of terminal DNA sequence modifications such as tag addition, insertions, deletions and mutations into the cloning strategy. Further, the restriction sites of the target plasmid can be either retained or removed.